2006
DOI: 10.1093/humrep/del418
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of magnetic-activated cell sorting and fluorescence-activated cell sorting in the decontamination of testicular cell suspensions in cancer patients

Abstract: MACS and/or FACS are insufficient for completely depleting testicular tissue of malignant cells. Although more research on alternative decontamination techniques is necessary, developing a reliable method to screen a priori testicular tissue for malignant cells may be equally important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
4
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 39 publications
4
88
4
3
Order By: Relevance
“…Although several experiments enabled the purification of human SG using surface markers such as ITGA6 [Geens et al 2007;Geens et al 2011;Conrad et al 2008], GPR125 [He et al 2010], stage-specific embryonic antigen-4 (SSEA-4) [Izadyar et al 2011], and KIT [von Schonfeldt et al 1999]. Other studies have also shown that when these strategies are used they often yield a population of cells that are contaminated with cancer cells [Geens et al 2007;Geens et al 2011;Jahnukainen et al 2011].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although several experiments enabled the purification of human SG using surface markers such as ITGA6 [Geens et al 2007;Geens et al 2011;Conrad et al 2008], GPR125 [He et al 2010], stage-specific embryonic antigen-4 (SSEA-4) [Izadyar et al 2011], and KIT [von Schonfeldt et al 1999]. Other studies have also shown that when these strategies are used they often yield a population of cells that are contaminated with cancer cells [Geens et al 2007;Geens et al 2011;Jahnukainen et al 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mass isolation of human stem spermatogonia (SG) in a safe way is not yet a feasible task [Goossens and Tournaye 2013]. Notwithstanding, several experiments enabled the purification of human SG using integrin alpha 6 (ITGA6) by using fluorescence-activated cell sorting (FACS) or magnetic-activated cell separation (MACS) [Geens et al 2007], MACS [Conrad et al 2008], or selection by selective matrix adhesion [Geens et al 2011]. The G protein-coupled receptor 125 (GPR125) [He et al 2010], the stage-specific embryonic antigen-4 (SSEA-4) [Izadyar et al 2011], and v-Kit Hardy-Zuckerman 4 Feline Sarcoma Viral Oncogene Homolog (KIT) [von Schonfeldt et al 1999] have also been successfully used for the isolation of human testicular stem SG by MACS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…have described an innovative dual positive (CD90+) and negative (CD45-) selection strategy that uses fluorescence-activated cell sorting (FACS) to purify SSCs from a contaminated sample of nonhuman primate testis cells prior to transplantation [4]. Their findings are promising, especially when compared to previous studies that report less successful results in filtering out malignant cells prior to cell transplantation into recipient mouse testes [6,7]. In preparing a suitable filtering protocol for clinical applications, however, absolute certainty of removing all potential malignant cells prior to transplantation is unattainable, and the inherent risk such a procedure carries should be carefully considered.…”
mentioning
confidence: 99%